ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA BERBASIS HOTS KELAS X SMA NEGERI 1 MAJENE - Fifi Alfiani; Ana Muliana M; Sitti Inaya Masrura (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to describe students' difficulties in solving HOTS-based math problems for Class X SMA Negeri 1 Majene. The approach used in this research is mixed methods. The research subjects used the purposive sampling technique, namely 5 students out of 30 students in class X MIPA 2 SMA Negeri 1 Majene. The research data was collected through HOTS-based math test questions and interviews. The research data were analyzed using quantitative analysis and qualitative data analysis. This study showed that the average score of the HOTS-based math test questions for class X MIPA 2 SMA Negeri 1 Majene was 28.1333. In addition, this study also showed that the subject categories were very low, low and were experiencing difficulties in solving problems including not being able to use concepts, problems and principles. In the high category subjects experienced several indicators of difficulty in solving problems including being unable to use concepts, verbal problems and principles. In the very high category subjects have no difficulty in solving questions including being able to use concepts, verbal problems and principles